Role of MRI-Based Functional Imaging in Improving the Therapeutic Index of Radiotherapy in Cancer Treatment - Li, Mei; Zhang, Qin; Yang, Kaixuan (Frontiers in Oncology, 2021)
Advances in radiation technology, such as intensity-modulated radiation therapy (IMRT), have largely enabled a biological dose escalation of the target volume (TV) while reducing the dose to adjacent tissues or organs at risk (OARs). However, the risk of radiation-induced injury increases with increasing radiation dose and area during radiotherapy (RT), which predominantly limits further increases in TV dose distribution and reduces the local control rate. In this regard, the accurate target delineation is crucial. Recently, technological improvements for precise target delineation have gained increasing attention in the field of RT. The addition of functional imaging to RT can provide a more accurate anatomy of the tumor and normal tissues (such as location and size), along with biological information aids to optimize the therapeutic index (TI) of RT. In the review, we discuss the application of some common MRI-based functional imaging techniques in clinical practice. In addition, we summarize the main challenges and prospects of these imaging technologies, expecting more inspiring developments and more productive research paths in the near future.